The effects of lifting straps in maximum strength, number of repetitions and muscle activation during lat pull-down - Valério, D. F.; Berton, R.; Barbieri, J. F.; Calzavara, J.; Moraes, A. C.; Barroso, R. (Sports Biomechanics, 2021)
The objective of the study was to investigate the effects of using lifting straps on the lat pull-down exercise on maximal strength, number of repetitions, and muscle activation. Twelve resistance-trained men participated (age 27 ± 4 years, body mass 84 ± 10 kg, height 177 ± 6 cm, resistance training experience 6.6 ± 2.4 years). All participants performed the 1RM tests and training protocols either with the lifting straps (WS) or without (WOS). Exercise sessions for both conditions (WS and WOS) consisted of 3 sets to concentric failure with a load of 70% of one repetition maximum (1RM) and rest intervals of 60 s. For the 1RM test, no difference was observed between WS and WOS conditions (96.5 ± 12.7 kg and 96.6 ± 11.9 kg, respectively). There were no differences between the WS and WOS conditions in the number of repetitions per set, total repetitions and latissimus dorsi muscle activation. In conclusion, the findings of this study demonstrate that the use of lifting straps in the lat pull-down exercise by resistance-trained individuals does not promote beneficial effect in the 1RM value, the number of repetitions performed with 70% of 1RM, and muscle activation.